If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + 17x + 66 = 0 Multiply x * x x2 + 17x + 66 = 0 Reorder the terms: 66 + 17x + x2 = 0 Solving 66 + 17x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (11 + x)(6 + x) = 0Subproblem 1
Set the factor '(11 + x)' equal to zero and attempt to solve: Simplifying 11 + x = 0 Solving 11 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + x = 0 + -11 x = 0 + -11 Combine like terms: 0 + -11 = -11 x = -11 Simplifying x = -11Subproblem 2
Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6Solution
x = {-11, -6}
| (x+6)(x-2)-(8x-7)=0 | | x*x*x+2x=4 | | n+4=0 | | 3r+4+3r=10 | | 8n-6+2n=14 | | 25y^2-80y+6= | | -3p+2p=4 | | 3x+17=32 | | k+4+3=1 | | 1.5c+c=20 | | x+1+6=6 | | k+7+8=19 | | 3x+2-6x=-7 | | -3m-8m=-11 | | -5x+x=4 | | -5n+3n=-10 | | 65-6X=12X+19 | | 9u^2-36v^2= | | 4+2a+6a=12 | | 4*x=60 | | 2n+5n=-21 | | 75x^3-12x=0 | | 49y^2-28y+4= | | v+1+4=10 | | m^3+6m^2-4m=0 | | a^2+8a-15=0 | | 116-4x=23x+17 | | ln(13)+ln(x)=0 | | 7b+1-b=1 | | x+7=-2(4x+10) | | 7-9x=46-30x | | 184-4x=41x+19 |